Legal Analysis Study Regarding Smoking According to an Islamic Legal Perspective - Mujahidin, Muhammad Bintang (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2021)
This article contains an analytical descriptive explanation regarding smoking laws. The significant smoking phenomenon is enough to be a strong reason that cigarettes have become an important need in society, even though some smokers only do it for fun. This article is the result of descriptive research that analyzes content related to smoking laws. In relation to the law on smoking, because it is basically a new thing that did not exist at the time of the Prophet, there is nothing in the Qur'an or hadith that discusses this in detail. Therefore, it is difficult to find a way out in determining legal certainty. The discussion of cigarettes starts from various arguments contained in the Al-Qur'an and Hadith in the form of mafhur and several opinions of scholars who try to analyze the meaning of cigarettes and the arguments used. Based on the arguments used in the proposed cigarette law, it can be concluded that the cigarette law is casuistic. Sometimes it can be said to be haram and sometimes makruh tanzih.